EFFECT OF WATER ACTIVITY, pH AND TEMPERATURE ON CONTAMINATION LEVEL OF DRIED VINE FRUITE BY FILAMENTOUS FUNGI DURING STORAGE (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
Growth of filamentous fungi in grape processing products depends on physical, chemical and biological factors. Our researches revealed high contamination level of dried vine fruit samples by filamentous fungi at high values of water activity. Definite correlation between values of acidity (pH) and sporulation level of dried vine fruit by filamentous fungi is revealed as well. The effect of temperature conditions of storage on mycobiota and contamination level of Armenian dried vine fruit by microscopic filamentous fungi is also studied. Storage of dried vine fruit in temperature lower then 4°С conditions promotes reduction of its sporulation degree by filamentous fungi.
Keywords: Filamentous fungi, water activity, acidity, sporulation degree, dried vine fruit